ASUHAN KEBIDANAN PADA NEONATUS NY “S” DI KLINIK UTAMA NILAM SARI TEMBILAHAN TAHUN 2019 - Diah utari; Yoneta Oktaviani (STIKES HUSADA GEMILANG, 2021)
Neonates are babies who have just undergone the birth process and must adjust from intrauterine to extra uterine life. In Indonesia in 2016 neonate deaths contributed to infant mortality by 59% at the age of 0-28 days, the neonatal mortality rate of Riau Province in 2018 recorded 393 cases and in INHIL regency in 2018 as many as 21 cases. Based on the data, neonatal visiting are important to reduce infant mortality by making a visit at least 3 times. This care aims to provide midwifery care to neonates in accordance with the management of Midwifery Care at Nilam Sari Tembilahan Main Clinic on July 01 to 15, 2019. The method of foster care uses varney's midwifery management and is documented in SOAP form. From the results of Neonatal midwifery care Mrs.